From an imperial stemma to a laurel wreath. Images of rulers on prince Lazar’s coinage - Odak Marina (Zograf, 2022)
The paper deals with the representations of rulers on the coinage of Prince Lazar while tracing the iconographic and insignological changes in the depiction of the prince, which reflected Lazar’s political program in different phases of his reign. Modeling his first representations on the dinars he minted on the coinage images of the emperors Dušan and Uroš, shaped on their money according to the formulas of Byzantine imperial images, after consolidating his power, Lazar gradually left the framework of the Byzantine ruler iconography and entered the sphere of the western monarchical image, culminating in the representation of the prince depicted in a profile bust with a laurel wreath, created under the influence of Hungarian coinage.